pH‐sensitive polymers: Classification and some fine potential applications - Ofridam, Fabrice; Tarhini, Mohamad; Lebaz, Noureddine; Gagnière, Émilie; Mangin, Denis; Elaissari, Abdelhamid (Polymers for advanced technologies, 2021)
Stimuli‐responsive materials in general and pH‐responsive polymers in particular have gained increasing interest during the last two decades. Their unique properties, which arise from their ability to exhibit sharp and reversible changes in response to environmental pH conditions, have made them suitable for various applications such as drug delivery and specific body‐site targeting, sensing and actuation, membrane functionalization, separation techniques, as well as in agriculture and food industry and even chemical industries. In the present review, the focus is on the general characteristics of pH‐responsive polymers in terms of their origin, chemical composition, and preparation. Moreover, some of the important and recent applications are reported and discussed.